Efectivity Test of Bitter Melon (Momordica charantia) and Bitter (Andrographis paniculata) Extract to T Lymphocytes Profile in Balb/C Mice - Vilansari, Novembya (Biotropika: Journal of Tropical Biology, 2015)
Type 2 diabetes mellitus (T2D) is a disease caused by the ineffectiveness of the body in using insulin. Intake of hypoglycemic drugs currently available only to control and normalize blood sugar levels but not to heal. The aim of this research was to confirm the effects of bitter melon (Momordica charantia) and bitter (Andrographis paniculata) extract on quantitative changes of CD4+TNF-Î±+ T cells. This research used 20 female mice as a probandus which were divided into 5 treatment groups: negative control, positive control, dose 1, dose 2 and dose 3. T2D was induced by STZ (streptozotocin) injection. T2D induced mice were treated with poly-herbal medicine extracts. After 14 days, spleen and liver cells were isolated for flow cytometry analysis. The analysis showed that ethanol extract of bitter melon (Momordica charantia) and bitter (Andrographis paniculata) can ameliorate type 2 diabetes mellitus mice model. This is proved by the decreasing ofÂ CD4+TNF-Î±+ after administration of the poly-herbal medicine. The poly-herbal medicine also lowers blood sugar levels in mice experiencing hyperglycemia. Â Keywords: Bitter, Bitter Melon, Diabetes Mellitus, STZ